Bradycardia and Heart Rate Fluctuation Are Associated with a Prolonged Intensive Care Unit Stay in Patients with Severe COVID-19 - Pattraporn Tajarernmuang; Konlawij Trongtrakul; Warawut Chaiwong; Teerapat Nantsupawat; Athavudh Deesomchok; Panida Chanayat; Nutchanok Niyatiwatchanchai; Theerakorn Theerakittikul; Atikun Limsukon; Chaicharn Pothirat; Chalerm Liwsrisakun; Chaiwat Bumroongkit (Medicina, 2022)
Background and Objective: Bradycardia has been observed among patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and is suspected to be associated with poorer outcomes. Heart rate (HR) fluctuation has been found to be correlated with a greater mortality rate in critically ill patients. The association of bradycardia and HR fluctuation with the outcome of severe coronavirus disease 2019 (COVID-19) patients has not been clarified. Therefore, we aimed to examine whether bradycardia and HR fluctuation correlated with poor outcomes in patients with severe COVID-19. Materials and Methods: We conducted a secondary analysis from a prospective data collection of patients admitted to the intensive care unit, between April and June 2021, at Chiang Mai University Hospital. Results: The results showed that 62 of 86 patients (72.1%) had bradycardia, defined by HR < 60 beats per minute (bpm). The number of patients with high HR fluctuation, defined as the difference in HR during admission ≥ 40 bpm, was greater among the bradycardia group than in the non-bradycardia group (70.9% vs. 14.7%, p = 0.015, respectively). The patients with bradycardia had greater levels of erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP). In addition, a greater proportion of patients with bradycardia received interleukin-6 inhibitors and hemoperfusion as a rescue therapy than those with non-bradycardia. After adjusting for age, gender, body mass index, CRP, and mechanical ventilator; bradycardia and the high HR fluctuation were significantly associated with a longer length of stay in the intensive care unit (ICU-LOS), with adjusted risk ratios of 2.67, 95% CI; 1.02, 6.94, p = 0.045 and 2.88, 95% CI; 1.22, 6.78, p = 0.016, respectively. Conclusion: We found that bradycardia and a high heart rate fluctuation were associated with a poorer ICU outcome in terms of longer ICU-LOS among the patients with severe COVID-19.